A Survey on Human Stress Monitoring Technique using Electrodermal Analysis - Sudarsan, P; Niranjil Kumar, A (International Journal of Computer Sciences and Engineering, 2019)
Stress management systems play a vital role in detecting the stress levels that disrupts an individual socioeconomic lifestyle. According to the World Health Organization (WHO), stress refers the mental health problem that affects the life of an individual. The stress levels can be measured based on the questionnaire by medical and physiological experts. This method fully depends on the answers given by individuals to detect whether they are stressed or not. During the past decades, Electrodermal Activity (EDA) analysis has been performed to measure the changes in the electrical conductivity of the skin. The changes in EDA may be produced by different physical and emotional stimuli that trigger variations in sweat-gland activity. To measure the changes in EDA, different sensors were also designed and many techniques have been developed to analyze the human stress. This paper presents a detailed survey of human stress detection based on EDA analysis to detect their stress levels. Initially, different stress detection methods using EDA analysis are studied in brief. Then, a comparative analysis is conducted to understand the drawbacks in those methods and suggest a new solution to enhance the stress and emotional monitoring system with high accuracy.